Perception and Attitude of Pregnant Women Towards Caesarean Section Delivery in University of Portharcoijrt Teaching Hospital, Rivers State - Grace C., Robinson-Bassey; Juliet U., Uchegbu (International Journal For Research In Health Sciences And Nursing, 2016)
The study aimed at determining perception and attitude of pregnant women towards caesarean section delivery in University of Port Harcourt Teaching Hospital, Rivers State. Three objectives, three research questions and two hypotheses were formulated to guide this study. A descriptive study design was used and using the Yaro Yamene formula for sample size determination, a sample size of’ 325 respondents was drawn from a target population of 1720 pregnant women attending antenatal clinic in UPTH. A simple random technique was used to draw respondents that participated in the study. A self structured questionnaire was used as the instrument of the study and a 92% return rate left the sample population of the study at 298 pregnant women. Data was presented on tables and analyzed using simple percentages, hypotheses were analyzed using chi-square test. Result showed that 186 (62.42%) respondents possessed a good knowledge, 61(20.47%) respondents possessed a fair knowledge while 51(17.11%) had a poor knowledge on caesarean section delivery; 103 (34.56%) respondents have positive perception while 195 (65.44%) respondents had a negative perception about caesarean section delivery. 125 (41.95%) respondents have positive attitude while 173 (58.05%) respondents had a negative attitude towards caesarean section delivery. Statistical analysis showed that there is a significant difference between respondents’ educational status and attitude as well as a significant difference between perception and attitude towards caesarean section delivery. It was recommended that the hospital management should take health education of pregnant women very seriously and Information, Education and Counseling should target pregnant women attending antenatal clinics in both group discussions and personal counseling sections.